Essentials of physical geography - Gabler, Robert E (Thomson Books/Cole, 2004)
The book creates the ultimate tool for illustrating physical geography concepts and helping students bridge the gap between scientific theory, practical application, and the human-environmental interface. The text emphasizes student involvement and interaction in the learning process, while combining the traditional and newer systems approaches. ESSENTIALS identifies and demonstrates three major roles for the discipline--Geography as a Physical Science, Geography as the Spatial Science, and Geography as Environmental Science